Epidemiology, potential risk factors and outcome of black fungus during COVID-19 pandemic: a concurrent prospective study at a dedicated COVID-19 hospital of North India - Mithilesh Kumar; Shipra Saini; Lokesh Parashar; Jaseetha Sasidharan; Pooja Goyal; Ratan Prakash Dhir (College of Community Physicians of Sri Lanka, 2022)
Introduction: As the number of COVID-19 patients increased during second wave, a steep rise of patients with mucormycosis was found in all parts of India. Objectives: To determine the epidemiological factors leading to the rise in fungal infection in patients during COVID-19 pandemic as well as describe the outcome of the disease during next three months after being discharged from the hospital Methods: It was a concurrent prospective study conducted between 26 June to 25 October 2021 at ESIC Medical College & Hospital, Faridabad, India. Patients positive for mucormycosis and agreed for the study were enrolled. They were interviewed telephonically after recording their consent. Results: A total of 51 patients were interviewed during our study period. During the follow-up, six patients died within three months of discharge from the hospital. The mean age of patients was 49.6years (SD=6.9 years), with the majority in the age group of 41-60 years. Most (53%) of the patients were males and 30(58.8%) were graduates and above. In the sample, 33 had a recent history of COVID-19 infection, 24 (47%) had been prescribed steroids, 16 (31.3%) had been prescribed oxygen during COVID-19 infection and 33(64.7%) were diabetic. The relationship of potential risk factors with the type of mucormycosis was not found to be statistically significant. Out of the45 patients who survived, 35 were better, three were still on oral anti-fungal treatment and seven patients required reconstructive plastic surgery. A significant association was found between patients who had a history of steroid intake and type of mucormycosis. Conclusions & Recommendations: Patients admitted to hospital with mucormycosis during the COVID-19 surge mostly had a history of COVID-19 infection, suffering from diabetes or on steroids. Most of the patients survived due to treatment availability (antifungal medicines, surgery or both) and about 15% of them had undergone long debridement surgery leading to severe loss of normal contour of the face and waiting for plastic reconstructive surgery.